Perspective of Intellectual Property Rights Related to Copyright in the Scope of Franchise Business - Urbanisasi Urbanisasi; Vania Clianta Putri (Asian Journal of Social and Humanities, 2023)
Franchise business is closely related to Intellectual Property Rights. Intellectual Property Rights, especially copyright, are exclusive rights that need to be protected because they are made based on the creativity, ideas, energy, and time of the creator. Legal protection of IPR in the franchise business is carried out to protect related parties from losses and actions that occur outside the franchise agreement. Indonesia itself has accommodated the need for IPR protection or exclusive rights with applicable laws and regulations. These laws and regulations not only protect the rights of the franchisor, but also regulate and protect the rights and obligations of the franchisee. In the international arena, Indonesia also participated in the Forum Agreement Establishing the World Trade Organization (Agreement on the Establishment of the World Trade Organization.